Medical education in Laos. (3rd August 2019) - Wittick, Timothy Alan; Bouphavanh, Ketsomsouk; Namvongsa, Vannyda; Khounthep, Amphay; Gray, Amy
Abstract: Medical education in Laos has undergone significant developments over the last century. A transition from a foreign to locally trained medical workforce has taken place, with international partners having an ongoing presence. Undergraduate and postgraduate medical education in Laos is now delivered by a single, government administered university. The transition to locally based training has had many flow-on benefits, including the retention of Lao doctors in the country and having graduates who are familiar with the local health system. A number of challenges do however exist. Medical resources in the Lao language are limited, teacher numbers and capacity are lacking and complex factors have led to a lack of uniformity in graduate competencies. Despite these challenges, the situation for medical education in Laos is a story of great optimism. Local staff has recognized the need for simple yet innovative solutions and processes are in place for the establishment of a licensing system for medical doctors and reforming existing curricula. Sustained, long-term relationships with partner organizations along with constructive use of technology are likely to be important factors affecting the future direction of medical education in Laos.